Pembuatan Alat Peraga Hydrophore Tank 3 Belokan 1 Katup Pipa 0,75 Inchi - Wibowo, Riyanto; Hariningrum, Rita (Marine Science and Technology Journal, 2023)
Fresh water is an important requirement in fixed or moving structures such as ships. One way to provide fresh water is through a hydrophore system. Hydrophore was chosen as an alternative to public water tower systems because water towers were considered less aesthetically pleasing. Another consideration is that every part of the ship should be taken care of so that it does not interfere with the performance of the ship. The ship chose the hydrophore system because this system is dimensionally more practical when compared to a water tower. The installation of a water basin on a ship must take into account the number of turns and valves in the outlet pipe. A hydrophore simulation tool with many bends and valves is required to predict the adequacy of water demand on board. This research was conducted to determine the conditions and obtain the specifications from the hydrophore system. The support created consists of 3 turns and 1 valve. The bus emission specification is 9x10-3 m3 with an inlet pipe flow rate of 391x10-6 m3/s and an outlet pipe flow rate of 343282x10-3 m3/s. Major head loss is 21x10-3 m and minor head is 0.7 m.